2016
DOI: 10.1007/s10620-016-4180-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Activity and Quality of Life Indices Are Valid Across Ulcerative Colitis But Not Crohn’s Disease Phenotypes

Abstract: Background Clinical activity and quality of life (QOL) indices assess disease activity in Crohn’s disease (CD) and ulcerative colitis (UC). However, a paucity of data exists on the validity of these indices according to disease characteristics. Aims To examine the correlation between QOL and clinical activity indices and endoscopic disease activity according to disease characteristics. Methods We used a prospective registry to identify CD and UC patients ≥18 years old with available information on Short In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…The best correlation was obtained for the Baron et al 18 score with left-sided colitis (SF, 0.503, P < .05; RB, 0.723, P < .001; and Seo et al 1 index, 0.688, P < .001). Taleban et al 35 consistently found a superior correlation between SCCAI and endoscopic disease activity in UC with left-sided disease compared with patients with extensive colitis (r ¼ 0.73 vs 0.45; P ¼ .005) (Supplementary Table 1).…”
Section: Association Between Clinical Symptoms and Endoscopy In The Dmentioning
confidence: 86%
See 2 more Smart Citations
“…The best correlation was obtained for the Baron et al 18 score with left-sided colitis (SF, 0.503, P < .05; RB, 0.723, P < .001; and Seo et al 1 index, 0.688, P < .001). Taleban et al 35 consistently found a superior correlation between SCCAI and endoscopic disease activity in UC with left-sided disease compared with patients with extensive colitis (r ¼ 0.73 vs 0.45; P ¼ .005) (Supplementary Table 1).…”
Section: Association Between Clinical Symptoms and Endoscopy In The Dmentioning
confidence: 86%
“…Active vs inactive disease. Overall, 8 studies only included patients with active disease (Lewis et al, 19 Dhanda et al, 20 Jharap et al, 21 Scaioli et al, 23 Seo et al, 3 Achitei et al, 24 Mirpour et al, 25 Jairath et al 1 ), whereas 15 studies included patients with both active and inactive disease (Bodelier et al, 26 Schoepfer et al, 27 Pagnini et al, 28 Beattie et al, 7 Azzolini et al, 12 Hirai et al, 29 Langhorst et al, 30 Arai et al, 31 Higging et al, 32 Ricanek et al, 33 Samuel et al, 34 Taleban et al, 35 Falvey et al, 36 Chen et al, 37 and Colombel et al 22 ). Unfortunately, the published data do not provide information for active vs inactive disease separately.…”
Section: Association Between Clinical Symptoms and Endoscopy In The Dmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an ongoing prospective cohort of adult patients diagnosed with CD, UC, or IBD-unspecified (IBDU) receiving care at the Massachusetts General Hospital Crohn’s and Colitis center 2225 . Upon obtaining informed consent, a detailed questionnaire assessing disease and treatment related information was completed by interview with a trained clinical research coordinator and confirmed by review of the medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to Crohn"s Disease (CD) symptom-based disease activity indices correlate fairly well with endoscopic and biometric grading of activity 1,2,3, 4 …”
mentioning
confidence: 99%